Probing aspects of extracellular vesicle associated AAV allows increased vector yield and insight into its transduction and immune-evasive properties - Ming Cheng; Demitri de la Cruz; Adam V. Crain; Paula Espinoza; Carrie Ng; Zachary C. Elmore; Aravind Asokan; Casey A. Maguire (Molecular Therapy: Methods & Clinical Development)
Extracellular vesicle-associated adeno-associated virus vectors (EV-AAVs) are generated during production in 293 cells. EV-AAV provides desirable gene delivery traits such as greater resistance to antibody neutralization and increased transduction of organs in vivo compared with conventional AAV. Despite these promising data, better characterization of EV-AAV is needed. We used density gradient ultracentrifugation to separate EV-AAV from free AAV to determine the yields and functional activity of EV-AAV. We found that the fraction of EV-AAV to conventional AAV in culture media from six AAV serotypes ranged from 0.5% to 12%. Next, we assessed whether intraluminal EV-AAV9 could mediate functional transduction of cells and observed that a portion of EV-AAV9 are intraluminal and mediated transduction of cultured cells in vitro and in vivo and evade antibodies compared with conventional AAV9. We tested whether trans-expression of membrane-associated accessory protein (MAAP) from AAV8 (MAAP8) or AAV9 (MAAP9) with AAV9 Cap/AAV9 MAAP null would alter yields of EV-AAV9. Trans-expression of MAAP8 or MAAP9 increased yields of EV-AAV9 compared with the cis-expression of AAV9 Cap/AAV9 MAAP. Finally, we found that the capsid was required for efficient transduction of cultured cells by EV-AAV. In sum, these data provide a foundation for the development of EV-AAV vectors.